2020
DOI: 10.18632/aging.103571
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive enhancement of healthy older adults using hyperbaric oxygen: a randomized controlled trial

Abstract: More than half of community-dwelling individuals sixty years and older express concern about declining cognitive abilities. The current study’s aim was to evaluate hyperbaric oxygen therapy (HBOT) effect on cognitive functions in healthy aging adults. A randomized controlled clinical trial randomized 63 healthy adults (>64) either to HBOT(n=33) or control arms(n=30) for three months. Primary endpoint included the general cognitive function measured post intervention/control. Cerebral blood flow (CBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 63 publications
3
24
0
Order By: Relevance
“…Increased CBF and higher oxygen delivery can improve or boost brain function. HBOT induces cognitive enhancement in both young [ 67 ] and elderly healthy subjects through regional changes in CBF [ 68 ]. HBOT has also been shown to increase CBF and improve EEG measurements [ 34 ], global cognitive scores [ 33 , 69 ] and PET scans [ 70 ] of post-stroke and TBI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increased CBF and higher oxygen delivery can improve or boost brain function. HBOT induces cognitive enhancement in both young [ 67 ] and elderly healthy subjects through regional changes in CBF [ 68 ]. HBOT has also been shown to increase CBF and improve EEG measurements [ 34 ], global cognitive scores [ 33 , 69 ] and PET scans [ 70 ] of post-stroke and TBI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperbaric oxygen therapy is a well-established treatment modality for non-healing wounds, radiation injuries as well as different hypoxic or ischemic events (such as carbon monoxide toxicity, infections, etc). In recent years, a growing evidence from pre-clinical as well as clinical trials demonstrate the efficacy of HBOT for neurological indications including idiopathic sudden sensorineural hearing loss [ 34 ], post stroke and post traumatic brain injury [ 35 41 ], central sensitization syndrome such as fibromyalgia syndrome [ 42 , 43 ] and age related cognitive decline [ 17 ] and animal models of Alzheimer’s disease [ 44 ]. For the first time, the current study aimed to evaluate the physiological effect on the cellular level in aging humans without any functional limiting disease.…”
Section: Discussionmentioning
confidence: 99%
“…The study cohort included only patients treated by HBOT, which is part of a larger cohort of normal ageing population studied at the Shamir medical center, Israel (NCT02790541 [ 17 ]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hachmo et al [ 195 ] reported the effect of hyperbaric oxygen in the prevention of telomere shortening and immunosenescence by the clearance of senescent immune cells. In this line, other studies have reported the same results in the aging skin, through the acceleration of epidermal basal cells proliferation [ 196 ], in the endothelial cells, where it induces antioxidants expression [ 197 ] and also in the brain, where HBOT appears to improve the cerebral blood flow [ 198 ], restoring cognitive parameters, hippocampal functions and even improved insulin resistance in both normal-weigh and obese aging rats [ 199 ].…”
Section: Translational and Potential Applications Of Hbotmentioning
confidence: 73%